2020
DOI: 10.1080/15538362.2020.1834899
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Changes in Weight and Sugar Content of Cactus Pear [Opuntia Ficus-indica (L.) Mill.] Fruit under Integrated Handling Practices

Abstract: The experiment was conducted to determine the effect of integrated postharvest chemical, packaging and storage treatments on weight loss and sugar content of cactus pear fruits. The treatments were factorial combinations of chemical (Control, 0.022 mM Salicylic Acid, and 27 mM CaCl 2 ), two packaging (unpackaged and packaged with polyethylene sheet) and two storage condition (ambient and evaporative cooler (EC)) in completely randomized design with three replications. Temperature and relative humidity of stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The fruits employed in this study were sourced from a company located in the south of Portugal, in the Alentejo region (Latitude: 38.74000562683715, Longitude: 7.815030812780606), that produces fruits of a regional "orange" variety (Figure 1). years, studies have been conducted concerning the storage of prickly pear fruits; however, most of these studies either use minimally proceeded fruits or edible coatings [22][23][24]. Furthermore, there are not many studies involving the usage of biodegradable plastics.…”
Section: Materials 211 Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruits employed in this study were sourced from a company located in the south of Portugal, in the Alentejo region (Latitude: 38.74000562683715, Longitude: 7.815030812780606), that produces fruits of a regional "orange" variety (Figure 1). years, studies have been conducted concerning the storage of prickly pear fruits; however, most of these studies either use minimally proceeded fruits or edible coatings [22][23][24]. Furthermore, there are not many studies involving the usage of biodegradable plastics.…”
Section: Materials 211 Fruitsmentioning
confidence: 99%
“…Further investigation is thus needed to assess how long it is possible to commercialize the fresh prickly pears with good organoleptic and nutritional quality, using simple and applicable storage methodologies, such as modified atmosphere packaging. In recent years, studies have been conducted concerning the storage of prickly pear fruits; however, most of these studies either use minimally proceeded fruits or edible coatings [22][23][24]. Furthermore, there are not many studies involving the usage of biodegradable plastics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quick spoilage nature of the fruits and limited value addition practices in the area causes substantial loss of this high-value food security crops and diminishes the farmers’ income. It has been identified that cactus pear fruit can be processed into jelly, jam and juice ( Shumye Adilu et al., 2020 ) in order to reduce its postharvest loss and enhance its diversity for people usage. But, there was no sufficient scientific data and literatures in Ethiopia, particularly in the Tigray region that indicate the suitability and usage of cactus pear fruit in value addition practices.…”
Section: Introductionmentioning
confidence: 99%